O tradycji literackiej w poezji Mirona Białoszewskiego - Kula, Aneta (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2001)
In the history of Miron Białoszewski as a poet the main issues are on the exploitation of commonplace and the continuation of literary tradition of low and high culture. Apart from the mentioned traditional literary genres, allusions to certain literary texts and the visible traces of Hindu ideas, one can correspondingly find here references to the Biblical symbolism, the combination of elements from various artistic spheres and polemics with traditional literary patterns. In my study I described some particular references to high literary culture and presented the examples of metatextual and intertextual references to such culture. At the same time I strove to explain the poet’s motives for using them.